2007
DOI: 10.1623/hysj.52.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of limited streamflow data on the efficiency and the parameters of rainfall—runoff models

Abstract: Streamflow data are essential for the calibration of continuous rainfall-runoff (RR) models. The quantity and quality of streamflow data can significantly influence parameter calibration and thus model robustness. Most existing sensitivity analysis studies on the role of streamflow data have used continuous periods to calibrate model parameters, with a minimum of one year, though ideally much longer periods are generally advised. However, in practical model applications, streamflow data series available for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
149
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 40 publications
15
149
0
3
Order By: Relevance
“…C1). Several studies showed that humid circumstances enhance the calibration process (Melsen et al, 2014;Perrin et al, 2007;Yapo et al, 1996, e.g. ), which can explain why so many parameters were classified as behavioural in these basins.…”
Section: Discussionmentioning
confidence: 99%
“…C1). Several studies showed that humid circumstances enhance the calibration process (Melsen et al, 2014;Perrin et al, 2007;Yapo et al, 1996, e.g. ), which can explain why so many parameters were classified as behavioural in these basins.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated usefulness of limited data (e.g. Vogel and Kroll, 1991;Burn and Boorman, 1993;Binley and Beven, 2003;Wagener et al, 2003;McIntyre and Wheater, 2004;Laaha and Blöschl, 2005;Rojas-Serna et al, 2006;Perrin et al, 2007;Seibert and Beven, 2009;Randrianasolo et al, 2011). On one hand, more research is needed to improve techniques in regionalisation and prediction in ungauged catchments, on the other hand, instrumentation and data assimilation technologies need to be advanced, along with other advancement in hydrological science, to reduce the number of completely ungauged catchments, improve understanding in physical processes of a catchment, and minimise predictive uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…We naturally do not advocate the intentional use of poor input data, but we consider that we need to document the impact of the progressive failure of a model when it encounters more and more input errors or missing values during its application or its calibration (see e.g. Oudin et al, 2006;Perrin et al, 2007).…”
Section: Large Data Sets and Data Qualitymentioning
confidence: 99%